Effectiveness Of Systematic Interactive Multimedia Instruction On Mastery Of Safety Knowledge And Emergency Procedures - Salameh, Zakariya Abdel Ghani (2012)
This study investigated the effectiveness of a systematic interactive multimedia instruction courseware with reflection and review in enhancing mastery of safety knowledge and skills in the aspects of Planned Emergency, Fire Fighting and First Aid, and self-efficacy among flight attendants. Eleven systematic interactive multimedia lessons were developed following Gagne‘s (1985) hierarchy of learning prescriptions and the steps of the Dick & Carey‘s (2001) instructional design model. Formative evaluation was conducted through a workshop with 28 flight attendants while the summative evaluation, as prescribed by the model, was conducted with the lessons integrated into the work routines of a group of flight attendants at an international airline. This study employed the randomized one group pre- and post-test design. Stringent controls were put into place to mitigate the threats to the research design. The sample for the summative evaluation study consisted of 35 flight attendants and supervisors in five crews which were randomly assigned to the study by the airline‘s scheduling department. Three instruments were constructed to collect the data, namely the Usability Questionnaire, the Safety Achievement Test and the In-Flight Safety Assurance Questionnaire. The flight supervisors conducted the reflection and review activities within the pre-flight briefing sessions before each flight. Data were analysed using one-sample t-test for the mastery scores and independent samples t-test for self-efficacy scores. The moderator variable was gender. Stringent controls were put into place to mitigate the threats to the research design.